VLSI architectural design tradeoffs for sliding-window log-MAP decoders. - Chien-Ming Wu (IEEE Transactions on VLSI systems)
Turbo codes have received tremendous attention and have commenced their practical applications due to their excellent error-correcting capability. Investigation of efficient iterative decoder realizations is of particular interest because the underlying soft-input soft-output decoding algorithms usually lead to highly complicated implementation. This paper describes the architectural design and analysis of sliding-window (SW) Log-MAP decoders in terms of a set of predetermined parameters. The derived mathematical representations can be applied to construct a variety of VLSI architectures for different applications. Based on our development, a SW-Log-MAP decoder complying with the specification of third-generation mobile radio systems is realized to demonstrate the performance tradeoffs among latency, average decoding rate, area/computation complexity, and memory power consumption. This paper thus provides useful and general information on practical implementation of SW-Log-MAP decoders.